2016
DOI: 10.1155/2016/6053510
|View full text |Cite
|
Sign up to set email alerts
|

Pricing Decisions of a Dual-Channel Closed-Loop Supply Chain under Uncertain Demand of Indirect Channel

Abstract: The dual-channel closed-loop supply chain (CLSC) which is composed of one manufacturer and one retailer under uncertain demand of an indirect channel is constructed. In this paper, we establish three pricing models under decentralized decision making, namely, the Nash game between the manufacturer and the retailer, the manufacturer-Stackelberg game, and the retailer-Stackelberg game, to investigate pricing decisions of the CLSC in which the manufacturer uses the direct channel and indirect channel to sell prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…Liu and Xu [6] proved that dual-channel collaborative pricing enabled avoiding risk effectively. Gao et al [7] established three price models on dual-channel closed-loop supply chain; the results showed that when customer's acceptance with the Internet channel increases, the wholesale price and retail price would decrease, while the optimal recycling transfer price was not affected. Huang and Swaminathan [8] studied four prevalent pricing strategies which differed in the autonomy degree for 2 Complexity the Internet channel.…”
Section: Introductionmentioning
confidence: 99%
“…Liu and Xu [6] proved that dual-channel collaborative pricing enabled avoiding risk effectively. Gao et al [7] established three price models on dual-channel closed-loop supply chain; the results showed that when customer's acceptance with the Internet channel increases, the wholesale price and retail price would decrease, while the optimal recycling transfer price was not affected. Huang and Swaminathan [8] studied four prevalent pricing strategies which differed in the autonomy degree for 2 Complexity the Internet channel.…”
Section: Introductionmentioning
confidence: 99%
“…Different CLSCs are studied under manufacturer-leader to investigate different topics such as the role of the players as marketing investor [118], recycling fund system [119], and the effect of risk [120]. However, some models compare the effect of two or three leaders (see, for instance, [14,58,[121][122][123][124][125] and [15,66,105,126,127] that consider triple and dual leaders, respectively). However, if the power difference between the parties is equal or minor, it can be studied through a Nash game.…”
Section: Game-based Clscsmentioning
confidence: 99%
“…e first related stream of the literature focuses on the online channel preference that includes Zhang et al [3], Guo et al [4], Zhu et al [5], Cai [11], Cao [12], Dumrongsiri et al [13], Dan et al [14], Gao et al [15], Hua et al [16], Huang and Swaminathan [17], Li et al [18], Lu and Liu [19], Ranjan and Jha [20], and Yoo and Lee [21]. For instance, Zhang et al [3] find that the channel selections are determined by the consumer's online acceptance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Li et al [18] find that, with the high consumer's online acceptance, the manufacturer provides customized products under the decentralized and centralized supply chain structures. Gao et al [15] and Lu and Liu [19] investigate how the consumer's online acceptance affects the dual-channel excepted profits and obtain that the consumer's online acceptances positively affect the manufacturer's profit, while the retailer's gain is the opposite. Ranjan and Jha [20] think over the effect of retailers' risk attitude and demand uncertainty on the pricing mechanism among dual-channel members.…”
Section: Literature Reviewmentioning
confidence: 99%